A biaxial stretchable, flexible electric heating composite film for de-icing. (November 2022) - Zhao, Zehui; Zhu, Yantong; Wang, Zelinlan; Zhang, Yi; Zhang, Kaiteng; Chen, Jichen; Liu, Xiaolin; Chen, Huawei
Graphical abstract: Highlights: A biaxially stretchable electric heating film was developed by combining conductive rubber materials with stretchable electrode. The stretchable electrode was prepared by silver plating on elastic fiber cloth. Kirigami structure was applied to reduce the tensile stress and electric resistance change during film stretching. The heating film has bidirectional tensile heating and deicing performance. Abstract: Icing on some flexible components which generally arises large deformation in work, such as air spring of high-speed rail and helicopter rotor, greatly threatens the safety of operation. Thus, flexible and stretchable de-icing capability are demanded to prevent ice accumulation on these flexible components. In this study, a novel flexible, biaxial stretchable electric heating film (BSF) with fast thermal response is developed for de-icing. The BSF was fabricated by combining conductive rubber materials with stretchable electrode which was prepared by silver plating on fiber cloth. To further reduce the tensile stress and resistance change of BSF, BSF with biaxial kirigami structure (BK-BSF) was explored, with excellent stretchable electro thermal performance, i.e., Joule heat can be generated when stretched by 40% along and perpendicular to the electrode directions. This study provides a feasible technical scheme for the anti-icing of flexible components.